How does user-generated content impact purchase intention through perceived food quality? - Juliyanti, Juliyanti; Rosnani, Titik; Purmono, Bintoro Bagus; Heriyadi, Heriyadi; Saputra, Pramana (Enrichment : Journal of Management, 2023)
The increasingly advanced digital world also impacts the changing of the way people around the world do business. Among them is the marketing approach, which is widely utilized on social media platforms such as YouTube, Facebook, Instagram, TikTok, and Twitter. This study aims to analyze the effect of User-Generated Content (UGC) on Eat Sambel purchase intention through perceived food quality. This type of research uses a quantitative approach with data collection methods through surveys in the form of questionnaires distributed online through Google Forms. The total sample of 215 respondents from Indonesia was selected based on the purposive sampling method with specified criteria. SEM Amos 24 is used to analyze data and test hypotheses. According to the study's findings, purchase intention was positively and significantly impacted by both User-Generated Content (UGC) and perceived food quality. User-Generated Content (UGC) also has a significant impact on perceived food quality. The results of this research are expected to improve the understanding of UGC and help online entrepreneurs